Shockwave treatment for medial tibial stress syndrome: A randomized double blind sham-controlled pilot trial. Issue 3 (March 2017) - Newman, Phil; Waddington, Gordon; Adams, Roger
Abstract: Objectives: Up to 35% of runners develop medial tibial stress syndrome (MTSS) which often results in lengthy disruption to training and sometimes affects daily activities. There is currently no high quality evidence to support any particular intervention for MTSS. This study aims to investigate the effect of shockwave therapy for MTSS. Design: A randomized, sham-controlled, pilot trial in a university-based health clinic including 28 active adults with MTSS. Methods: Intervention included standard dose shockwave therapy for the experimental group versus sham dose for the control group, delivered during Week 1–3, 5 and 9. Main outcome measures were pain measured during bone and muscle pressure as well as during running using a numerical rating scale (0–10) and running was measured as pain-limited distance (m), at Week 1 (baseline) and Week 10 (post-intervention). Self-perception of change was measured using the Global Rating of Change Scale (−7 to +7) at Week 10 (post-intervention). Results: Pain (palpation) was reduced in the experimental group by 1.1 out of 10.0 (95% CI −2.3 to 0.0) less than the control group. There were no other statistically significant differences between the groups. Conclusions: Standard dose shockwave therapy is not more effective than sham dose at improving pain or running distance in MTSS. However, the sham dose may have had a clinical effect. Further investigation including a no intervention control is warranted to evaluate the effect of shockwave therapy in the management of MTSS.